Burnout, Depression und Depersonalisation – Psychologische Faktoren und Bewältigungsstrategien bei Studierenden der Zahn- und Humanmedizin [Burnout, depression and depersonalisation – Psychological factors and coping strategies in dental and medical students] - Prinz, Patrick; Hertrich, Klaus; Hirschfelder, Ursula; de Zwaan, Martina (GMS Zeitschrift für Medizinische Ausbildung, 2012)
[english] Background: Previous studies found that stress, depression, burnout, anxiety, and depersonalisation play a significant role amongst dental and medical students. We wanted to examine if students of the University of Erlangen-Nuremberg also would report elevated values as can been found in similar publications. Furthermore, particularly coping strategies were investigated.Methods: The data collection took place in April 2008 including 182 dental and medical students of the 4 and 5 academic year at the University of Erlangen-Nuremberg. Demographic data and the following screening instruments were used: Maslach Burnout Inventory (MBI), Cambridge Depersonalisation Scale (CDS-9), Hospital Anxiety and Depression Scale (HADS), Brief COPE. Results: Descriptive statistics showed higher pathological values in dental students than in medical students. The difference was especially pronounced on the depersonalisation scale (CDS-9), with 20.4% of the dental students, but only 5.5% of the medical students showing scores above a cut-off of 19. The scores decreased in the course of 3 semesters of dentistry. The students with elevated values showed a higher degree of dysfunctional coping. Conclusion: Our results obtained with the screening instruments are in line with the results of previous investigations of other authors and point out the importance of this issue. It might be useful to develop programs teaching dental students more adaptive coping strategies before their first patient contact. [german] Hintergrund: Studien der vergangenen Jahre zeigten, dass Stress, Depression, Burnout-Syndrom, Angst und Depersonalisation während des Studiums der Zahn- und Humanmedizin einen besonderen Stellenwert einnehmen. Es stellt sich die Frage, ob auch bei Studierenden der Universität Erlangen-Nürnberg erhöhte Werte, wie sie in der Literatur gefunden werden, nachweisbar sind. Zudem soll untersucht werden, welche Arten von Bewältigungsstrategien vorkommen.Methodik: Die Datenerhebung fand im April 2008 bei 182 Studenten der Human- und Zahnmedizin des 4. und 5. Studienjahres an der Universität Erlangen-Nürnberg statt. Neben der demographischen Erhebung kamen folgende Screening Instrumente zum Einsatz: Maslach Burnout Inventory (MBI), Cambridge Depersonalisation Scale (CDS-9, Kurzversion), Hospital Anxiety and Depression Scale (HADS), Brief COPE. Ergebnisse: In der deskriptiven Statistik zeigten sich bei den Zahnmedizinstudenten erhöhte Werte im Vergleich zu den Humanmedizinstudenten. Besonders deutlich war der Unterschied bei den Werten der Depersonalisations-Skala (CDS-9). Es hatten 20.4% der Zahnmedizin- und nur 5,5% der Humanmedizinstudenten Werte über dem cut-off von 19. Im Querschnitt der drei Studiensemester Zahnmedizin nahm die Anzahl der Studierenden mit auffälligen Werten ab. Studierende mit auffälligen Werten zeigten ein höheres Maß an dysfunktionalen Bewältigungsstrategien. Schlussfolgerung: Die Messwerte der Screening Instrumente ähneln der Untersuchungen anderer Autoren und unterstreichen die Bedeutung der Thematik. Aus Sicht der Prävention könnte sich bei Studenten der Zahnmedizin die Zeit vor dem ersten Patientenkontakt anbieten, um geeignete Bewältigungsstrategien zu vermitteln.